PERSEPSI MASYARAKAT TERHADAP POTENSI MADU HUTAN DI DESA SEMUNTAI KECAMATAN KETUNGAU HILIR KABUPATEN SINTANG - Ariyani, Ria; Roslinda, Emi; Anwari, M Sofwan (JURNAL HUTAN LESTARI, 2019)
The Semuntai Villagers have preserved existing forest honey by not destroying the forest where honey is located, so it can be harvested several months to increase economic income for the villagers. The study of people’s perceptions of the potential of forest honey in Desa Semuntai, Kecamatan Ketungau Hilir, Kabupaten Sintang, has not been carried out, so the research on the forest honey is needed. The purpose of this study was to examine people’s perceptions of the potential of forest honey and examine the factors that influence the perceptions of the Semuntai villagers on the potential of forest honey. This study used a survey method with interview techniques that are assisted by questionnaires. The sampling was conducted using purposive random sampling technique. The data analysis was carried out by descriptive analysis and inferential analysis. The results showed that the people’s perception of the potential of forest honey in Desa Semuntai, Kecamatan Ketungau Hilir tended to be neutral, were people who knew the potential of forest honey and felt the benefits of forest honey themselves but did not understand the purpose and function itselves.The villagers that tended to have a moderate level of knowledge do not mean they have less understanding but are based on what they see. The highest income level is the medium category, which is Rp.8,795,513.70-Rp.16,186,024.76 with 50 respondents. The level of income respondents vary due to the different sources of income for each respondent, the main job of the dominant respondents is rubber farmers and farming as a side job. People who tend to have a moderate cosmopolitan level are people who have moderate knowledge of the potential of forest honey. They obtain and seek information from television or radio to get information about the potential of forest honey.Keywords: Community Perception, Potential Forest Honey, Semuntai